2014
DOI: 10.1111/acer.12333
|View full text |Cite
|
Sign up to set email alerts
|

Binge Drinking, Reflection Impulsivity, and Unplanned Sexual Behavior: Impaired Decision‐Making in Young Social Drinkers

Abstract: These results support the role of binge drinking in reduced impulse control and decision-making deficits. The findings indicate that high-binge drinkers demonstrate impairments on an impulse control task similar to that observed in dependent samples and this may be a factor in understanding the negative behavioral consequences associated with excessive alcohol use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
80
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 47 publications
7
80
1
2
Order By: Relevance
“…One personality trait that has been consistently correlated with binge drinking in the literature, especially among college students, is impulsivity (Balodis et al, 2009;Carlson et al, 2010;Caswell, Celio, Morgan, & Duka, 2016;Clark et al, 2012;Townshend, Kambouropoulos, Griffin, Hunt, & Milani, 2014;Wellman, Contreras, Dugas, O'Loughlin, & O'Loughlin, 2014). In the literature, impulsivity is considered a multifaceted concept (as noted in Caswell et al, 2016); however, most commonly impulsivity refers to a deficits in the ability to regulate present actions and plan proactively, or to favouring spontaneous behaviour over regard for future consequences.…”
Section: Impulsivitymentioning
confidence: 99%
See 4 more Smart Citations
“…One personality trait that has been consistently correlated with binge drinking in the literature, especially among college students, is impulsivity (Balodis et al, 2009;Carlson et al, 2010;Caswell, Celio, Morgan, & Duka, 2016;Clark et al, 2012;Townshend, Kambouropoulos, Griffin, Hunt, & Milani, 2014;Wellman, Contreras, Dugas, O'Loughlin, & O'Loughlin, 2014). In the literature, impulsivity is considered a multifaceted concept (as noted in Caswell et al, 2016); however, most commonly impulsivity refers to a deficits in the ability to regulate present actions and plan proactively, or to favouring spontaneous behaviour over regard for future consequences.…”
Section: Impulsivitymentioning
confidence: 99%
“…"Risky" Sexual Behaviour: Based on the association between binge drinking and disinhibition (or impulsivity), binge drinking has also been associated with risky sexual behaviour such as unprotected or unplanned sexual relations (Bersamin, Paschall, Saltz, & Zamboanga, 2012;Brown & Vanable, 2007;Connor, Psutka, Cousins, Gray, & Kypri , 2013;Orchowski, Mastroleo, & Borsari, 2012;Townshend et al, 2014). For example, Townshend et al (2014), in comparing low-binge drinkers (those who scored lower than the median binge drinking score of 28.5 on the Alcohol Use Questionnaire which factors in both quantity and frequency) to high-binge drinkers (those who scored higher than the median score), found that high-binge drinkers reported more instances of unplanned sexual encounters than their lower-level counterparts.…”
Section: Impulsivitymentioning
confidence: 99%
See 3 more Smart Citations